2020
DOI: 10.12688/f1000research.22525.1
|View full text |Cite
|
Sign up to set email alerts
|

Topical ozonated virgin coconut oil improves wound healing and increases HSP90α, VEGF-A, EGF, bFGF and CD34 in diabetic ulcer mouse model of wound healing

Abstract: Background: Diabetes is a disease that affects people worldwide, including in Indonesia. The prevalence of diabetes in Indonesia is increasing from year to year. One of the most devastating complications of diabetes mellitus is diabetic ulcers, which is a limb-threatening complication. Over the past few decades, ozone generated using plasma medical technology has been investigated as an agent that helps wound healing. This study aims to evaluate the effects of topical ozonated virgin coconut oil (VCO) in a dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…They found that the wound closure rate in the VCO group was higher on all days compared to diabetic nontreated rats, and VCO was found to be better than silver sulfadiazine cream in the healing of diabetic wounds via promoting re-epithelialization and collagen synthesis, as well as increasing WCR and total protein content. A few other studies reported the effectiveness of pure VCO (liquid form) in promoting the healing process [ 45 , 46 , 47 ]. The wound healing potency of fermented virgin coconut oil was also verified against human umbilical vein endothelial (HUVEC), fibroblast (CCD-18), and retinal ganglion (RGC-5) cells, as well as a wound excision model in Sprague–Dawley rats [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…They found that the wound closure rate in the VCO group was higher on all days compared to diabetic nontreated rats, and VCO was found to be better than silver sulfadiazine cream in the healing of diabetic wounds via promoting re-epithelialization and collagen synthesis, as well as increasing WCR and total protein content. A few other studies reported the effectiveness of pure VCO (liquid form) in promoting the healing process [ 45 , 46 , 47 ]. The wound healing potency of fermented virgin coconut oil was also verified against human umbilical vein endothelial (HUVEC), fibroblast (CCD-18), and retinal ganglion (RGC-5) cells, as well as a wound excision model in Sprague–Dawley rats [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…with O 3 therapy (Eroglu et al, 2019;Yuniati et al, 2020). Prostacyclin (PGI2) and nitric oxide (NO) are potent vasodilators that play key roles in the maintenance of vascular homeostasis (Mitchell et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Medical ozone was generated by using a DDBD plasma generator which consists of two Pyrex glass barriers separated by 3 mm from each other (13,14) . This type of DDBD is known to generate high ozone purity, as the barriers keep the electrodes from corrosion, preventing the produced ozone from contamination (14) .…”
Section: B Medical Ozone Generatormentioning
confidence: 99%
“…(4,6,(8)(9)(10) Ozone bagging therapy for diabetic foot ulcers is beneficial as an anti-microbial effect, increasing glycemic control, increasing insulin sensitivity, preventing oxidative stress, increasing fibroblast proliferation, and increasing the release of growth factors such as PDGF, TGF-β, and VEGF which make the wound healing process faster and more effective. (10,12,13) The use of ozone bagging for diabetic foot ulcers abroad has been widely used. (6,9,10) But in Indonesia, is still not widely used, while the Medical Ozone Generator device found by researchers in Indonesia has met the standards for use as an adjuvant therapy for diabetic foot ulcers.…”
Section: Introductionmentioning
confidence: 99%